Vibration-based damage detection for a composite helicopter main rotor blade. (June 2016) - dos Santos, F.L.M.; Peeters, B.; Van der Auweraer, H.; Góes, L.C.S.; Desmet, W.
Abstract: This work presents experimental results of two damage detection techniques based on modal properties, with the application on a full-size composite helicopter main rotor blade. The damage detection methods used in this study are the coordinate modal assurance criterion (COMAC) and the modal strain energy method, which are respectively based on the comparison of vibration modes and on the comparison of the modal strain energy of a beam. Modal parameters were obtained with experimental modal analysis and damage was introduced artificially on the blade by attaching a small mass to it, changing its global properties in this way. Finally, experimental results for the damage detection technique are shown for both methodologies, and remarks concerning sensitivity and robustness of the methods are discussed.